Investigation to Characterise Field Pests That Affect Bean Plants in Lowlands and Uphills of Mwanjari Parish Southwestern Division Kabale District. - Wakayiya, Derick (Kabale University, 2024)
The study aimed to document knowledge about bean field pests affecting bean plants in Mwanjari Parish, Southern Division, Kabale District, Southwestern Uganda. The ultimate goal was to improve pest control or eradication strategies to enhance bean production, ensuring food security and increased income through higher sales. The study focused on identifying field pests that damage bean plants, analyzing the impacts of these pests on the plants, and providing recommendations for mitigating their effects. A survey design guided by the study's objectives was employed. Mwanjari Parish was selected due to its highland terrain, which is well-suited for bean cultivation. The primary objective was to understand the impact of field pests on bean production. Data was collected from 16 randomly selected farmers, highlighting that beans serve as a staple food and a source of income in the parish. The majority of farmers preferred climbing beans over bush varieties due to their superior advantages. In addition to pest challenges, farmers reported other constraints in bean production, including a lack of staking materials for climbing beans, labor shortages, and bean diseases. Results revealed that 87.5% of the farmers were in the active labor age range of 21–50 years, providing the workforce needed for bean farming. Furthermore, 68.75% of farmers cultivated beans during the second season, which offers high yields due to moderate rainfall. The study identified insects, such as aphids and bean leaf beetles, as the predominant field pests causing damage at various stages of bean growth. The findings underscore the need for breeding and selecting pest-resistant bean varieties as a sustainable solution to mitigate pest-related challenges. This approach would significantly enhance bean production in Mwanjari Parish and Kabale District, contributing to food security and economic growth.